APLIKASI TRANSFORMASI GEOMETRI PADA ETNOMATEMATIKA TENUN SIAK - Mefa Indriati; Turmudi Turmudi; Jarnawi Afgani Dahlan (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Siak weaving is a work of art resulting from the manufacture of songket cloth by craftsmen in Siak Sri Indrapura, Riau Province. This fabric has a variety of motifs, displaying the characteristics of Riau Malay culture. The motifs on Siak woven fabrics are generally taken from the natural environment, such as plants, animals, and other natural objects, which are then twisted (transformed) into interesting motifs, arranged systematically that form geometric patterns. Descriptive qualitative research was conducted, by collecting data and information related to Siak woven motifs through observation and interviews with parties at the Siak woven fabric production center. Identification is carried out on all existing Siak woven fabric motifs to find out whether there is an application of geometric transformation in these woven fabric motifs. From the results of observation and identification, as many as 58 types of motifs were obtained in siak weaving. If observed carefully, the pattern of the arrangement of the motifs of the fabric, there are actually rhythmic and patterned properties of regularity. Some forms of regularity patterns on Siak woven fabrics are applications of geometric transformations. Some are in the form of reflection, rotation, translation, and dilatation.